Practical‐Political Jurisprudence and the Dual Nature of Law. (1st August 2013) - Nason, Sarah
Abstract Law contains many dualities, though most, if not all, of these dualities resolve into one complex puzzle: To what extent is law a matter of pure social facts, or moral value untethered to social facts? I argue that each concept of law reconciles this duality in a different way on the basis of certain beneficial consequences that might result. Instead of pitting concepts against one another universally, we should accept that the balance between law's social fact and moral value dimensions is context‐specific in relation to particular legal puzzles. This balance can be achieved only by considering both political theory and empirical data.